2007
DOI: 10.1002/ana.21078
|View full text |Cite
|
Sign up to set email alerts
|

DNA single‐strand break repair is impaired in aprataxin‐related ataxia

Abstract: This study provides the first direct evidence for the functional involvement of APTX in SSBR and in vivo DNA damage in EAOH/AOA1, and suggests a benefit of antioxidant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 38 publications
(72 reference statements)
5
41
0
Order By: Relevance
“…A clear defect in cellular SSB repair, however, has only been reported for mutations in TDP1, as the attempts to demonstrate a similar defect in AOA1 failed to give consistent results. While aprataxin knock down appears to delay resealing of SSBs accumulated under conditions of GSH depletion (Hirano et al, 2007), other studies failed to detect slower repair kinetics of lesions caused by H 2 O 2 in AOA1 cells carrying different APTX mutations (Gueven et al, 2004) or in APTX knock out chicken DT40 cells, APTX -/-mouse fibroblasts, AOA1 human fibroblasts and AOA1 lymphoblast cell lines (Reynolds et al, 2009a). It was thus hypothesized that lack of consistent defects in SSB repair in aprataxin-defective cells, may reflect either the low abundance of 5'-AMP breaks or the availability of other factors for repair of these types of lesions (El-Khamisy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clear defect in cellular SSB repair, however, has only been reported for mutations in TDP1, as the attempts to demonstrate a similar defect in AOA1 failed to give consistent results. While aprataxin knock down appears to delay resealing of SSBs accumulated under conditions of GSH depletion (Hirano et al, 2007), other studies failed to detect slower repair kinetics of lesions caused by H 2 O 2 in AOA1 cells carrying different APTX mutations (Gueven et al, 2004) or in APTX knock out chicken DT40 cells, APTX -/-mouse fibroblasts, AOA1 human fibroblasts and AOA1 lymphoblast cell lines (Reynolds et al, 2009a). It was thus hypothesized that lack of consistent defects in SSB repair in aprataxin-defective cells, may reflect either the low abundance of 5'-AMP breaks or the availability of other factors for repair of these types of lesions (El-Khamisy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…SSBR is known to be impaired in aprataxin knocked-down cells (Hirano et al, 2007) and a defect in cellular SSBR has also been reported in some AOA1 patient's derived cells (Mosesso et al, 2005;Gueven et al, 2007). Aprataxin is indeed recruited at sites of SSBs in an XRCC1-dependent manner and the targeting is mediated by PARP-1, a protein interacting with both XRCC1 and aprataxin and working as key player in SSBs detection (Harris et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of all the known FHA domains, the FHA domain of PNK shares the highest sequence similarity with aprataxin, a product of the APTX gene mutated in the neurological disorder ataxia-oculomotor apraxia, that is involved in SSB repair [57][58][59][60][61]. In PNK the FHA domain serves a targeting role, directing PNK to the site of DNA damage by binding to phosphorylated XRCC1 and XRCC4, key components of the BER and NHEJ pathways, respectively.…”
Section: The Fha Domainmentioning
confidence: 99%
“…One of the most robust set of data that demonstrates association between DNA repair and neurodegenerative diseases comes from studies on early onset ataxia with ocular motor apraxia and hypoalbuminemia/ataxia with oculomotor apraxia type 1 (EAOH/AOA1), an autosomal recessive form of cerebellar ataxia caused by mutations in the aprataxin (APTX) gene. It was shown that aprataxin participates in DNA repair suggesting that genes involved in DNA repair pathways might have a role in neurodegeneration (Hirano et al, 2007;Takahashi et al, 2007). Also parkin, encoded by one of the causative genes of Parkinson's disease (PD), seems to contribute to DNA repair (Kao, 2009).…”
Section: Introductionmentioning
confidence: 99%